Individualism–Collectivism in Hofstede and GLOBE - Brewer, Paul; Venaik, Sunil (Journal of International Business Studies, 2011)
This paper examines the Individualism–Collectivism (I-C) dimension of national culture in the Hofstede and GLOBE models. We identify major contradictions between the two culture models, which result in contradictory relationships with external variables such as economic prosperity. We critically evaluate the content validity of the items used to measure this construct in both models. Based on our analysis, we suggest that Hofstede's Individualism–Collectivism index be relabelled as Self-orientation vs Work-orientation and GLOBE's In-group collectivism as Family Collectivism. We demonstrate how the proposed alternative conceptualizations of the Individualism–Collectivism dimensions in both the Hofstede and GLOBE models can help reconcile the anomalous relationships between these two models of national culture, and between their dimension scores and other external variables of interest to researchers. We recommend a way forward for future research incorporating the collectivism dimensions that identifies which of the Hofstede/GLOBE scores is appropriate for differing purposes. This will help to make future research findings clearer, and to reduce contradictions and anomalies. Implications drawn from such research should also be clearer as a result.